A case of isolated renal involvement of polyarteritis nodosa successfully treated with steroid monotherapy. (20th July 2016) - Pourafshar, Negiin; Sobel, Eric; Segal, Mark
Abstract : Polyarteritis nodosa (PAN) is a systemic necrotising vasculitis that affects medium-sized and small-sized arteries. The spectrum of disease ranges from involving a single organ to polyvisceral failure. We report a case of a 75-year-old male presented with solely hypertension and mild renal function impairment as a consequence of diffuse renal necrotising vasculitis with occlusive but non-stenotic lesions associated with PAN. The overall prognosis of PAN has been improved in recent decades, primarily reflecting early diagnosis and more effective treatments. Therefore, early diagnosis is critical and it warrants full investigations even in those patients without obvious multiorgan manifestations. In those instances, with mild disease, steroid monotherapy has been shown to be effective with excellent response. Our patient responded well to steroid monotherapy and we were able to gauge his response by improvement in his blood pressure.